Macroarray expression analysis of cytokines and prostaglandin metabolism–related genes in chronic rhinosinusitis - Aiko Oka, MD; Kengo Kanai, MD; Takaya Higaki, MD; Seiichiro Makihara, MD; Yohei Noda, MD; Shin Kariya, MD; Mizuo Ando, MD; Wataru Nishimura, MD; Mitsuhiro Okano, MD (Journal of Allergy and Clinical Immunology: Global, 2023)
Background: Chronic rhinosinusitis (CRS) can be divided into endotypes by functional or pathophysiologic findings. Objective: The aim of this study was to analyze the expression of cytokines, prostaglandin (PG) synthases, and their receptors related to the pathogenesis of CRS, especially those contributing to nasal polyp (NP) formation. Methods: NPs and uncinate tissue (UT) samples were collected from 90 patients who underwent endoscopic sinus surgery. They included 75 patients with CRS (including 45 with eosinophilic CRS [eCRS] and 30 with non-eCRS) and 15 patients without CRS. A total of 30 genes were selected for our original DNA array plate to analyze the levels of expression of 10 cytokines (IFN-γ, IL-4, IL-5, IL-10, IL-13, IL-17A, IL-22, IL-25, IL-33, and TSLP), 4 prostaglandin synthases (prostaglandin D2 [PGD2] synthase, prostaglandin E2 synthase, COX-1, and COX-2), and their 16 receptors. Clustering analysis was performed according to the expression results, and clinical findings of patients from each cluster were investigated. Results: The samples could be divided into 3 clusters. Cluster 1 showed elevated levels of expression of IL4, IL5, IL13, TSLP, IL1RL1 (ST2 [an IL-33 receptor]), HPGDS, and GPR44 (CRTH2, a PGD2 receptor); cluster 2 showed elevated levels of expression of IL17A and PTGES; and cluster 3 showed an elevated level of expression of IL25. Regarding clinical features, the main characteristics of each cluster were as follows: NPs from patients with eCRS for cluster 1, NPs and/or UT samples from patients with non-eCRS for cluster 2, and UTs from patients with non-CRS for cluster 3. Conclusion: The results suggest that there are associations between type 2 inflammation/PGD2 and eCRS and also between type 3 inflammation/prostaglandin E2 and non-eCRS.